GAMBARAN SIKAP DAN PERILAKU PENCEGAHAN COVID-19 PADA PENYINTAS COVID-19 DI INSTALASI PELAYANAN JANTUNG TERPADU RSUD DR. SAIFUL ANWAR MALANG - Andhix Eko Cahyono; Ns. Wiwik Agustina; Nanik Susanti (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study aims to describe the attitudes and behavior of Covid-19 survivors in an effort to prevent Covid-19 in Malang City, especially in the IPJT RSSA Malang room. This study was designed as a quantitative research with a descriptive design approach by conducting a survey on the attitudes and behavior of Covid-19 survivors at the Integrated Cardiac Service Installation at RSUD Dr. Saiful Anwar Malang. With a population in the study of 42 people. The sample in this study were 15 respondents with non-probability sampling techniques. Data collection techniques using a questionnaire. The results of this study indicate that all respondents have a good attitude as many as 15 respondents (100%) and more than half of the respondents as many as 11 (73.33%) most of the respondents behave positively, and a small proportion of respondents 4 (26.66%) behave fairly. Joint efforts are needed to maintain a good attitude and the formation of positive behavior in an effort to prevent Covid-19 in Covid-19 survivors, on the basis of understanding and joint efforts, it is hoped that related parties will optimize health protocols so that they can prevent the transmission of Covid-19 to Covid-19 survivors until the pandemic is over.